Role of Sit-Tight Syndrome in Undermining Democratic Institutions in Nigeria: A Governance Perspective - Olaoye Olumuyiwa Joseph; Joshua Kayode Okunade (Matondang Journal, 2026)
This research paper investigates the role of the "sit-tight syndrome" in undermining democratic institutions in Nigeria from a governance perspective. Despite Nigeria's transition to democratic rule in 1999, the persistence of this syndrome—characterized by political leaders' attempts to extend their tenures beyond legitimate limits—has systematically weakened key democratic institutions such as the judiciary and electoral management bodies. The study reveals that sit-tight syndrome manifests through various mechanisms, including electoral manipulation, suppression of opposition, and the use of state resources to maintain political dominance, leading to a significant decline in electoral integrity and political participation. Findings indicate a troubling trend of increasing voter apathy, exemplified by the lowest voter turnout recorded in the 2023 elections, and a detrimental impact on governance outcomes, including service delivery failures and heightened corruption. The research employs a theoretical framework that integrates elite theory, institutional path dependency, and democratic consolidation theory to elucidate the mechanisms through which sit-tight syndrome perpetuates itself and exacerbates Nigeria’s democratic challenges. The study concludes with actionable recommendations aimed at addressing constitutional vulnerabilities, enhancing institutional integrity, and fostering civic engagement, underscoring the necessity for a cultural transformation in political accountability and participation to ensure the future stability of Nigeria's democracy.